Development and evaluation of an Android-based multimedia application to promote healthy lifestyles in physical education: A study at State Junior High School 29 Semarang - Pujiyanto, Galang Yusuf; Royana, Ibnu Fatkhu; Wibisana, Muh. Isna Nurdin (CV Rezki Media, 2025)
Background: The integration of interactive, technology-based media in Physical Education, particularly for teaching health-related content, remains limited despite its potential to enhance student engagement and learning outcomes. Objectives: This study aims to address this gap by developing and evaluating the effectiveness of an Android-based multimedia learning application,